Distance between distance spectra of graphs. Issue 12 (2nd December 2017) - Lin, Huiqiu; Li, Dan; Das, Kinkar Ch.
Abstract: Let be a connected graph with vertex set and edge set E ( G ). Let D ( G ) be the distance matrix of G and be its distance spectrum. The distance between distance spectra of G and is defined by Define the cospectrality of G by Let . In the paper, we obtain lower bounds on and for . Furthermore, we give an upper bound on .